COMPOSING OF ORIGIN–DESTINATION TRIP MATRIX FOR TRANSIT TRAFFIC FLOW ACROSS THE CENTRAL BUSINESS PARTS OF THE METROPOLIS - E. Getsovich (Avtomobilʹnyj Transport (Harʹkov), 2014)
The problem of selecting the type of vehicle functions in the problem of calculating the gravitational transit flows is considered. The use of computational procedure of Shatsky–Sheleyhovsky to clarify the relationship of gravity distance between transport areas by comparing the matrix correspondence before and after balancing is proposed.